Conhecimento de professores sobre a Síndrome de Burnout : processo, fatores de risco e consequências - Diehl, Liciane (2014)
The Burnout Syndrome (BS) has been considered one of the most important occupational health problems of psychosocial character in society. Severity among teaching professionals puts the teaching activity as one of the high-risk professions, in view of the individual, institutional and social repercussions. This dissertation consists of two empirical studies of qualitative design and set out to explore the knowledge of teachers about the Burnout Syndrome, as well as understand the factors used to interpret this process. The I study, titled "Burnout Syndrome: indicators for the construction of a diagnosis", aimed at understanding and identify, through detailed and systematic information, within a real life context, the elements that characterize the BS. Still, we tried to check the signs that characterize the process of diagnosis of BS from the categories Illusion at Work, Wear Psychological Indolence and Guilt, dimensions of BS related to the theoretical model proposed by Gil-Hill (2005). The II study, " Knowledge about Teacher Burnout Syndrome: process, risk factors and consequences", intended for knowledge about Burnout, its symptoms, its development process, risk factors, consequences and possibilities of intervention and investigated the meaning of teaching from the perspective of the teacher, with participation of six teachers of elementary school. From the first study, it was possible to identify elements that form the four dimensions of the theoretical model and the presence of indicators of profile 1, which, added to the sense of guilt, indicate the presence of indicators that characterize the profile 2, more severe clinical picture Burnout. Effective measures taken by the respondent prevented the occurrence of burnout and quitting the profession. The II study results showed is still incipient their understanding of BS, complicating diagnosis and treatment. Pointed out the need for clarification on the signs and symptoms of BS to the worker, as well as healthcare professionals, to the correct diagnosis. Recommendations are also thinking and planning effective intervention measures especially informative about their risk factors, possible expulsion for treatment and financial compensation.